Tension-free tape IVS (intravaginal sling) in surgical treatment of urinary stress incontinence – first experience - Wlaźlak, Edyta; Surkont, Grzegorz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2003)
There are known a lot of operations used for genuine stress incontinence (GSI) treatment. Lately tension-free vaginal slings are becoming widely used. One of new types of the tape is intravaginal sling – IVS (Tyco). Objectives. The aim of this study is analysis of IVS procedure course and perioperative period. Defining complications and validation the influence of the treatment on quality of life will allow us to optimize and standardize the procedure. Materials and methods. IVS was performed in 31 women aged 38–82 years (mean 56.6). Diagnosis was defined according to the result of urogynecology examination, done corresponding to special questionnaire, 7-days voiding diary, 1-hour pad test and urodynamic assessment. The influence of the disease and treatment on quality of life was estimated with the use of King’s College Hospital questionnaire. IVS operation was performed under spinal anesthesia after hydrodessection the retropubic space. After small vaginal and abdominal incisions, emptying bladder and placing Foley catheter with metal probe into bladder, according to prof. Petri’s suggestions, we slowly and delicate introduced tape with trochars. We did cystoscopy 2 times. Foley catheter was inserted for 24 hours. Post-voiding urine retention was controlled. Results. 22 times we performed IVS as single operation. 9 women had combined procedure. 35% patients informed about previously done operations in small pelvis. We had no case of bladder perforation. We noticed no voiding problems. Two patients had transient (a few hours) haematuria. Two women submit urethritis. Hospitalization time, besides 2 cases, was 2 days. In one case during cystoscopy we found small vesical mucosa damage without perforation This happened during combined procedure. First we removed uterine cervix (patient was after supravaginal uterus excision) and performed kolporrhaphy. After 3 weeks of Foleys catheterization, during cystoscopy we noticed healed mucosa. In one patient after 40 minutes after IVS done as single procedure, we found during external abdominal examination haematoma (about 10 cm in diameter). It was emptied through vagina. Tape was not removed. Perioperative period was without other complications. After 1 month patient started to complain urgency. After 3 months from the IVS procedure tape was cut regarding post-voiding urinary retention. This finished voiding and urge problems. Continence was sustained. Conclusions/Discussion. IVS is relatively safe and well-tolerated procedure considering among other things short time of hospitalization. IVS operation is done behind symphysis in „darkness”, with no possibility to avoid penetration through vessels. No case of bladder perforation in our patients may be the effect of hydrodessection, plastic end of IVS needle and delicate, slowly placing trochars. These conclusions need to be confirmed during more extensive studies.